Analisis Pelaksanaan Tugas Pokok dan Fungsi Satuan Polisi Pamong Praja dalam Penegakan Peraturan Daerah di Kabupaten Pinrang - Muhammad Rifad Syarif Putra; Andi Gau Kadir; Nurlinah Nurlinah (Departemen Ilmu Pemerintahan Fisip Unhas, 2009)
Abstract: This study aims to describe how the role of the civil service in the police force to maintain order and peace in Pinrang in accordance with the duties and functions and the factors that affect the government's role in the maintenance of order and peace in Pinrang . This type of research used in this study is descriptive case study research base. The results showed that the role of civil service police unit to enforce the Regulation area not be separated from how the form of oversight of regional regulations carried out in accordance with the Basic Tasks and Functions as regulation enforcement , this is in accordance with the duties and functions of the police force officials civil set out in Regulation Regent No. 10 Year 2008 on the Implementation of the Regional Regulation No. 18 of 2008 on the Organization and Work Procedures Government Technical Institute Pinrang. Keywords: the civil service in the police, order, peace, reginonal regulation.Abstrak: Penelitian ini bertujuan menguraikan bagaimana peran satuan polisi pamong praja dalam menjaga ketertiban dan ketentraman di Kabupaten Pinrang sesuai dengan tugas pokok dan fungsinya dan faktor- faktor yang mempengaruhi peran pemerintah dalam penjagaan ketertiban dan ketentraman di Kabupaten Pinrang. Dari hasil penelitian menunjukkan bahwa Peran Satuan Polisi Pamong Praja dalam menegakkan Peraturan Daerah tidak lepas dari bagaimana bentuk pengawasannya terhadap Peraturan Daerah yang dijalankan sesuai dengan Tugas Pokok dan Fungsinya sebagai penegak perda, hal ini sesuai dengan tugas dan fungsi satuan polisi pamong paraja yang diatur dalam Peraturan Bupati No. 10 Tahun 2008 Tentang Pelaksanaan Peraturan Daerah No. 18 Tahun 2008 tentang Organisasi dan Tata Kerja Lembaga Teknis Daerah Pemerintah Kabupaten Pinrang.Kata kunci: satuan polisi pamong praja, ketertiban, penegakan, peraturan daerah